Women's work, health, and empowerment - Gandhi, Anjali (Delhi Aakar, 2006)
Contributed articles on women issues in India; also includes a brief report on the Seminar.
"This book is a result of recommendations of the Seminar on "National Policy of Empowerment of Women" jointly organized by Sarojini Naidu Centre for Women's Studies and Department of Social Work, Jamia Millia Islamia, New Delhi"--T. p. verso.
Includes index.
Keywords: Feminism -- India -- Congresses; Women in development -- India -- Congresses; Women -- Health and hygiene -- India -- Congresses